Exosomes and Their Role in Cancer Progression - Liu, Yang; Shi, Ke; Chen, Yong; Wu, Xianrui; Chen, Zheng; Cao, Ke; Tao, Yongguang; Chen, Xiang; Liao, Junlin; Zhou, Jianda (Frontiers in Oncology, 2021)
Exosomes from extracellular vesicles can activate or inhibit various signaling pathways by transporting proteins, lipids, nucleic acids and other substances to recipient cells. In addition, exosomes are considered to be involved in the development and progression of tumors from different tissue sources in numerous ways, including remodeling of the tumor microenvironment, promoting angiogenesis, metastasis, and invasion, and regulating the immune escape of tumor cells. However, the precise molecular mechanisms by which exosomes participate in these different processes remains unclear. In this review, we describe the research progress of tumor cell-derived exosomes in cancer progression. We also discuss the prospects of the application of exosomes combined with nanoengineered chemotherapeutic drugs in the treatment of cancer.